PENGELOLAAN KUALITAS AIR TERHADAP KELANGSUNGAN HIDUP UDANG VANAME (Litopenaeus vannamei) PADA TAMBAK INTENSIF DI CV KURNIA TIRTA MAKMUR PROBOLINGGO, JAWA TIMUR (PENDEKATAN KOMPARATIF) - Resky Aulia; Ilyas; Budiman Haruna (JURNAL ILMIAH PENELITIAN MAHASISWA, 2026)
This study aimed to analyze the differences in water quality management and the survival rate (SR) of whiteleg shrimp (Litopenaeus vannamei) cultured in ponds B2 and B3 at the intensive farming facility of CV Kurnia Tirta Makmur Water quality was recognized as a critical factor influencing shrimp growth, health. and survival in intensive aquaculture systems. The study employed a quantitative approach using a comparative research method. The samples were selected using a purposive sampling technique, consisting of ponds B2 and B3 during one production cycle. Data were collected through field observations and direct measurements of water quality parameters, including temperature, pH, salinity. water transparency, and survival rate (SR). The data were analyzed descriptively and further evaluated using an Independent Samples t-test at a 5% significance level. The results showed that pH, salinity, water transparency, and survival rate did not differ significantly hetween ponds B2 and B3 (p > 0.05). In contrast, water temperature showed a significant difference (p0.050), although the recorded temperatures in both ponds remained within the optimum range for whiteleg shrimp culture. The survival rate reached 87.68% in pond B2 and 95.23% in pond B3. indicating that both ponds achieved good production performance. It was concluded that water quality management in both ponds met the company's operational standards and effectively supported the survival of whiteleg shrimp. despite the observed difference in water temperature.